PERAN TRUSTWORTHINESS, PERCEIVED RISK, DAN INFORMATION QUALITY TERHADAP CUSTOMER SATISFACTION DALAM PEMBELIAN ONLINE MONOKROMSTORE JOGJA - Ida Bagus Nyoman Udayana; Agus Dwi Cahya; Rizqi Rukmana Putri (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
The industrial era 4.0 with technology used is increasingly sophisticated and in various fields so as to change people's lifestyles, they tend to prefer to use technology for transactions rather than going directly to shopping places. This study aims to determine the effect of Trustworthiness, Perceived Risk and Information Quality on Customer Satisfaction in purchasing Fashion Online at Monkromstore Jogja. This study uses quantitative research methods. The sample used for this study was 100 respondents. The sampling technique in this study is purposive sampling with the criteria that respondents have an account for online purchases at Monokromstore Jogja and respondents have made online purchases at Monokromstore Jogja. The results in this study indicate that Trustworthiness has a significant and significant effect on Customer Satisfaction on online fashion purchases at Monokromstore. Perceived Risk has a significant and significant effect on Customer Satisfaction on online fashion purchases at Monokromstore Jogja. Information Quality has no significant effect on Customer Satisfaction on online fashion purchases at Monokromstore Jogja. Trustworthiness, Perceived Risk, and Information Quality simultaneously have a significant effect on Customer Satisfaction in purchasing online fashion at Monokromstore Jogja